2016
DOI: 10.1002/tox.22290
|View full text |Cite
|
Sign up to set email alerts
|

Tissue deposition and toxicological effects of commercially significant rare earth oxide nanomaterials: Material and physical properties

Abstract: Rare earth oxide (REO) materials are found naturally in earth's crust and at the nanoscale these REO nanoparticles exhibit unique thermal, electrical, and physicochemical properties. REO nanoparticles are widely used in different industrial sectors for ceramics, glass polishing, metallurgy, lasers, and magnets. Recently, some of these REO nanoparticles have been identified for their potential application in medicine, including therapy, imaging, and diagnostics. Concurrent research into the REO nanomaterials' t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Among these nanomaterials, CeO 2 NP have been reported to exhibit antioxidant effects by scavenging free radicals in cells, and exerting catalytic effects by mimicking superoxide dismutase (SOD) and catalase activities 12,37 . The redox properties and toxicity of CeO 2 NP are affected by their size, morphology, surface chemistry, and other factors, such as additives that coat the surface, local pH, and ligands that can participate in redox reactions 38,39 . CeO 2 NP can internalize in human and animal cell lines and tissues and then localize with mitochondria, lysosomes and endoplasmic reticula as well as being abundant in the cytoplasm and the nucleus, thereby imparting protection against various oxidants 40,41 .…”
Section: Discussionmentioning
confidence: 99%
“…Among these nanomaterials, CeO 2 NP have been reported to exhibit antioxidant effects by scavenging free radicals in cells, and exerting catalytic effects by mimicking superoxide dismutase (SOD) and catalase activities 12,37 . The redox properties and toxicity of CeO 2 NP are affected by their size, morphology, surface chemistry, and other factors, such as additives that coat the surface, local pH, and ligands that can participate in redox reactions 38,39 . CeO 2 NP can internalize in human and animal cell lines and tissues and then localize with mitochondria, lysosomes and endoplasmic reticula as well as being abundant in the cytoplasm and the nucleus, thereby imparting protection against various oxidants 40,41 .…”
Section: Discussionmentioning
confidence: 99%
“…This is most likely due to aggregation to micrometer sized particles causing them to become trapped in the capillary beds of the lungs on first pass, similar to what is seen with the liver/lung imaging agent, 99m Tc macroaggregated albumin ( 99m Tc-MAA), and in a study of the biodistribution of uncoated rare earth oxide NPs. 22,54 Increased uptake in the liver and spleen, representing endocytic sequestration of NPs in the reticuloendothelial system (RES), is seen with all [ 89 Zr]-CONPs and is common to the biodistribution of NPs. 27,55 PET dynamic imaging revealed that [ 89 Zr]-CONP-DT10-NH 2 had the most immediate and highest uptake in the liver, likely due to its strong positive surface charge facilitating uptake.…”
Section: Discussionmentioning
confidence: 99%
“…19-21 CONPs also have shown low in vivo toxicity, which has been shown to decrease with smaller size. 22-24 With their low toxicity profile, diverse biological activities and potential pharmacological promise for clinical applications, it is prudent to utilize CONPs’ multi-functional nanoparticle (NP) platform to adjust their physicochemical properties through modified synthesis and study their pharmacokinetics through imaging to tailor them toward their intended biological application.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is parenteral route, but unlike intravenous injection, the drug delivery is much slower. 44 Therefore, intravenous injection usually uses lower doses of nanoparticles that is usually under 5 mg/kg for CNPs, [45][46][47] but in intraperitoneal injection, it is safer if higher doses were used. 48 Herein, we want to show that CNPs are safe following acute administration.…”
mentioning
confidence: 99%